Anti-Epileptic Effect of Crocin on Experimental Temporal Lobe Epilepsy in Mice - Zhong, Kai; Qian, Chengyu; Lyu, Rui; Wang, Xinyi; Hu, Zhe; Yu, Jie; Ma, Jing; Ye, Yilu (Frontiers in Pharmacology, 2022)
Temporal lobe epilepsy (TLE) is a common kind of refractory epilepsy. More than 30% TLE patients were multi-drug resistant. Some patients may even develop into status epilepticus (SE) because of failing to control seizures. Thus, one of the avid goals for anti-epileptic drug development is to discover novel potential compounds to treat TLE or even SE. Crocin, an effective component of Crocus sativus L., has been applied in several epileptogenic models to test its anti-epileptic effect. However, it is still controversial and its effect on TLE remains unclear. Therefore, we investigated the effects of crocin on epileptogenesis, generalized seizures (GS) in hippocampal rapid electrical kindling model as well as SE and spotaneous recurrent seizure (SRS) in pilocarpine-induced TLE model in ICR mice in this study. The results showed that seizure stages and cumulative afterdischarge duration were significantly depressed by crocin (20 and 50 mg/kg) during hippocampal rapid kindling acquisition. And crocin (100 mg/kg) significantly reduced the incidence of GS and average seizure stages in fully kindled animals. In pilocarpine-induced TLE model, the latency of SE was significantly prolonged and the mortality of SE was significantly decreased by crocin (100 mg/kg), which can also significantly suppress the number of SRS. The underlying mechanism of crocin may be involved in the protection of neurons, the decrease of tumor necrosis factor-α in the hippocampus and the increase of brain derived neurotrophic factor in the cortex. In conclusion, crocin may be a potential and promising anti-epileptic compound for treatment of TLE.